Pengaruh Corporate Social Responsibility dan Good Corporate Governance pada Agresivitas Pajak dengan Manajemen Laba sebagai Pemoderasi - Arianti, Baiq Fitri; Hadisah, Susi (Gorontalo Accounting Journal, 2025)
This study was conducted with the aim of analyzing the effect of Corporate Social Responsibility and Good Corporate Governance on Tax Aggressiveness with Earnings Management as a Moderating Variable. This type of research uses quantitative methods. The population in this study were Property and Real Estate companies listed on the Indonesia Stock Exchange. The samples used in this study amounted to 12 Property and Real Estate companies with a 5-year observation period in the 2019-2023 period. The results of the research conducted show Corporate Social Responsibility, has an effect on Tax Aggressiveness, Good Corporate Governance has no effect on Tax Aggressiveness, Earnings Management is able to moderate Corporate Social Responsibility    on Tax Aggressiveness and Earnings Management is not able to moderate Good Corporate Governance on Tax Aggressivenes.